EFFECT OF HIBISCUS ROSA-SINENSIS LINN. EXTRACTS ON THE AMOUNT, MOTILITY, MORPHOLOGY, VABILITY OF SPERMATOZOA OF MALE RATS (RATTUS NORVEGICUS) - Julia, Dina; Salni, salni; Nita, Sri (Biomedical Journal of Indonesia, 2019)
The participation of men in family planning is still relatively low when compared to the participation of women. One of the traditional medicinal plants used is antifertility hibiscus flowers. This study aims to examine the effect of hibiscus flower extract on the number, motility, morphology and viability of spermatozoa of male rats (Rattus norvegicus). This research is an experimental study using a completely randomized design (CRD). The sample in this study used 25 male Sprague Dawley strains aged 60-70 days with a body weight of 200-210 grams. Duration of treatment for 30 days at a dose of 200 mg / kg, 300 mg / kg, 400 mg / kg. Data is presented in the form of tables and diagrams and narration to interpret the data. The results of this study indicate a decrease in sperm count in the treatment group compared to the control group (p = 0,000), a decrease in sperm motility (p = 0.001), an abnormal morphological increase (p = 0,000), and a decrease in spermatozoa viability between the treatment groups compared to the group control (p = 0,000). It can be concluded that there is a significant difference in the effect of hibiscus flower extract on the number, motility, morphology, viability of spermatozoa.